Exergaming in the car: Preliminary results of an experimental setup - Krome, S.; Walz, Steffen; Greuter, S.; Gerlicher, A.; Schleehauf, M. (2014)
This paper presents a pilot study that explores an experimental setup for measuring stress reduction through an exergaming approach within the spatial limitations of a car. Besides our focus on the exploration of the experiment's setup, we present preliminary results that are crucial for the design of gameful stress reduction in the car context. We conclude that winning or losing an exergame does not have a significant effect on the player's distress level. However, the exergame itself, if designed properly for the spatial limitation of the car, does have a significant influence on the player's level of distress, worry and engagement.